Is There a Future for Branch Campuses? - Altbach, Philip (International Higher Education, 2011)
Branch campuses are a growing worldwide phenomenon. This article discusses the various elements of the branch campus movement, defines branch campuses, and analyzes some of the problems and challenges involved.